A comparative study of intra operative parameters of darning and mesh repair in inguinal hernia - V., Mahesh S.; K., Hota P.; D., Abhishek (International Surgery Journal, 2016)
Background: Inguinal hernias are protrusions of abdominal cavity contents through the inguinal canal. Inguinal hernias are the commonest of all hernias and adult inguinal herniorrhaphy accounts for 15% of operations in general surgery. Surgery is the definitive treatment for the hernia. If hernias are not operated, often they go for complications and increase the morbidity and mortality. The objectives of the study were to compare intra operative parameters of darning and mesh repair in inguinal hernia. Methods: This prospective controlled study was conducted in 50 patients presenting with inguinal hernia. The 50 patients were randomly allocated into two groups. Group A consists of 25 patients who underwent darning and Group B of 25 patients who underwent Lichtenstein mesh repair. Detailed history, thorough general, local and relevant systemic examination was carried out with all necessary investigations. After obtaining informed consent patients were subjected to surgery. Various intra-operative and post-operative parameters were noted. Patients were followed post-operatively closely to note the complications. Data was entered and analyzed using chi square test. P value of less than 0.05 was considered significant. Results: The incidence of inguinal hernia was more in patients with Strenuous work as it accounted for 14 i.e. 46.6% of the patients with precipitating factors and 28% of the study sample. All patients presented with swelling and only 38% of the patients presented with swelling with pain. Both the groups were compared for post-operative pain and post-operative complications and it was found that there was no significant difference among the two groups. But cost wise, the darn repair technique is more cost effective than mesh repair. Conclusions: The present study revealed that the cost effectiveness of darning for inguinal hernia as the cost of darning is almost half of mesh repair with similar results.